2020
DOI: 10.3389/fenrg.2020.565542
|View full text |Cite
|
Sign up to set email alerts
|

Solar Desalination Using Fresnel Lens as Concentrated Solar Power Device: An Experimental Study in Tropical Climate

Abstract: Solar desalination is a renewable energy-driven method that produces freshwater from saline/brackish water. Conventional solar desalination units are equipped with an inclined transparent condensing plate placed over a feedwater basin containing saline water. The process is limited to a small quantity of production because of scattered solar irradiation and the unavailability of solar heat due to intermittent cloudy weather. In this study, a Fresnel lens has been used to concentrate solar energy onto a spot to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Feedwater's local temperature and evaporation rate were both increased using a Fresnel lens, as described by Choong et al (2020) [36]. The feedwater was focused on using flat Fresnel lenses mounted atop a double-sloped passive solar still.…”
Section: Gang Et Al (2019)mentioning
confidence: 99%
“…Feedwater's local temperature and evaporation rate were both increased using a Fresnel lens, as described by Choong et al (2020) [36]. The feedwater was focused on using flat Fresnel lenses mounted atop a double-sloped passive solar still.…”
Section: Gang Et Al (2019)mentioning
confidence: 99%
“…In fact, polystyrene nonwoven has outperformed PET and polyamide textile systems in solar distillation, producing more distilled water by absorbing more distillation by-product water vapor. Textile-based solar distillation is being researched for desalination and wastewater treatment plants, offering the potential to provide clean water to underserved communities while improving system efficiency and sustainability 22 , 23 , 39 .…”
Section: Introductionmentioning
confidence: 99%
“…For both BSSS and TSSS, the application value depends on its fresh water yield performance. The methods to improve the fresh water yield of the BSSS and TSSS include adding a solar concentrator (Choong et al, 2020), designing a multi-stage still (Yeang et al, 2023), increasing the evaporation area by adding sand troughs (Nagaraju et al, 2022), adding the nanofluids (Sangeetha et al, 2022), and so on. In a study by Tiwar (Tiwar, 1988), it is concluded that the daily fresh water yield and the purity of the fresh water from a horizontal tubular solar seawater still (HTSSS) are higher than that from a BSSS under the same condition.…”
Section: Introductionmentioning
confidence: 99%